It is Hard for Journalists to Pray on Time: Commodification of Media Workers in the Digital Age - Muhammad Nur Rohman (Kalijaga Journal of Communication, 2023)
This study aims to explain the commodification practices of media workers in the digital era, more precisely on iNews TV Semarang, Indonesia. This research uses a qualitative approach with a case study method. Data collection techniques were carried out in the form of observations and interviews with people who work as journalists at iNews TV Semarang. This study shows that journalists experience commodification in the form of absolute exploitation and relative exploitation. Absolute exploitation is seen in the irregular working hours of journalists, resulting in chaos during their worship hours. At the same time, relative exploitation is in the form of intensification of the labor process for journalists, which is carried out by giving multiple assignments. Journalists also get another task: looking for clients for the company's benefit. The commodification that has occurred has also involved processes of alienation, mystification, naturalization, and reification.